ANTIMICROBIAL SUSCEPTIBILITY OF COAGULASE-NEGATIVE STAPHYLOCOCCI ISOLATED FROM CONJUNCTIVAL CONTENTS - Valentyn P. Kovalchuk; Kateryna Yu. Hrizhymalska; Sviatoslav O. Sandurskyi; Artur S. Skrypka (Клінічна та профілактична медицина)
Introduction. Opportunistic pathogens, which normally vegetate on the conjunctival mucosa, are involved in the development of perioperative infectious complications in ophthalmic practice. When examining the contents of the conjunctival sac of healthy individuals by the culture technique, coagulase-negative staphylococci, which are always present on the eyelid skin, are most often isolated in small quantities. Bacteria of this genus belong to opportunistic pathogens, since with mechanical, chemical or thermal injury to the skin or mucous membranes, they are actively engaged in the development of an inflammatory reaction.